If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2(x + 3) + -1x = x + 5 Reorder the terms: 7 + -2(3 + x) + -1x = x + 5 7 + (3 * -2 + x * -2) + -1x = x + 5 7 + (-6 + -2x) + -1x = x + 5 Combine like terms: 7 + -6 = 1 1 + -2x + -1x = x + 5 Combine like terms: -2x + -1x = -3x 1 + -3x = x + 5 Reorder the terms: 1 + -3x = 5 + x Solving 1 + -3x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + -3x + -1x = 5 + x + -1x Combine like terms: -3x + -1x = -4x 1 + -4x = 5 + x + -1x Combine like terms: x + -1x = 0 1 + -4x = 5 + 0 1 + -4x = 5 Add '-1' to each side of the equation. 1 + -1 + -4x = 5 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = 5 + -1 -4x = 5 + -1 Combine like terms: 5 + -1 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| n+n+(n-3+4)+4n=4n | | 6x^2+15x-25=0 | | f-f+9f-(f-3)=f+f | | 4m-12m+(m-3)=2m | | 3x+14+2x-4=90 | | -2-5(r-2)=-3(1-2r) | | 156-5x=31x+20 | | .833333x-.2x+4=.7x | | 506-?=265 | | 7(2n-4)-5=-40+7n | | 4ln(x-4)=4 | | (p+3)x^2+(2p+3)x+p+5=0 | | -.4x-9=.9 | | 5x+14=-28x-9x | | 19-3e=2-5(e+1) | | (y^2+2)(4y+7)= | | 2r^2+3r-20=0 | | (3y-3)(y+3)= | | 5x-3=2+6x | | 7=2r+5r | | -129=-3(8-7p) | | (y+9)(y+6)= | | 5x+1=14x-73 | | 6d-2(d-2)=3(d-12) | | (x+7)(2x^2-6x-2)= | | 5b-3=7b+11 | | 4x+10y=35 | | x(5-x)+4(x^1)= | | (5x-6)(4x-7)= | | (5x-7)(3x-2)= | | -7=12-k | | 4d-3=21 |